Derivative of Trig Function using quotient rule Help

Hey guys need some help here. The trig identities are killing me so far this semester. i have to use the quotient rule. Here is the problem and where i have gotten to.

y= sinx+cosx/cosx

y'= f'g-fg'/g^2

= {[(cosx-sinx)(cosx)]-[(sinx+cosx)(-sinx)]}/cos^2x

= (cos^2x-sinxcosx)-(-sin^2x-sinxcosx)/cos^2x

=(cos^2x-sinxcosx+sin^2x+sinxcosx/cos^2x

=cos^2x+sin^2x/cos^2x

= (cos^2x/cosx)+(sin^2x/cosx)

= am i even close. thanks for the help

Re: Derivative of Trig Function using quotient rule Help

Quote:

Originally Posted by

**psilver1** y= sinx+cosx/cosx

y'= f'g-fg'/g^2

= {[(cosx-sinx)(cosx)]-[(sinx+cosx)(-sinx)]}/cos^2x

= (cos^2x-sinxcosx)-(-sin^2x-sinxcosx)/cos^2x

=(cos^2x-sinxcosx+sin^2x+sinxcosx/cos^2x

=cos^2x+sin^2x/cos^2x

This is correct. To simplify the expression use the identity .

Note that

and